2020
DOI: 10.1002/csr.2022
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility intensity, management earnings forecast accuracy, and investor trust: Evidence from Japan

Abstract: This study examines whether and how corporate social responsibility (CSR) intensity affects investment performance directly, as a signal of investor trust, and indirectly, by impacting management earnings forecasts accuracy. We find that investors benefit from high CSR firms as they avoid unexpected stock volatility while paying the cost of CSR by lowering returns. The results suggest that CSR intensity stabilizes stock returns for high CSR firms in the long run and moderates management disclosure bias in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 77 publications
0
9
0
2
Order By: Relevance
“…As the competitive landscape has changed in the current era, it was reported that both the consumers and investors now consider the social engagement of an organization before making a purchase or investment decision. In this regard, several studies have reported that socially responsible organizations, irrespective of the size or sector, are well placed in the current competitive landscape compared to the organizations that do not adopt responsible practices [62,136,137].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the competitive landscape has changed in the current era, it was reported that both the consumers and investors now consider the social engagement of an organization before making a purchase or investment decision. In this regard, several studies have reported that socially responsible organizations, irrespective of the size or sector, are well placed in the current competitive landscape compared to the organizations that do not adopt responsible practices [62,136,137].…”
Section: Discussionmentioning
confidence: 99%
“…Referring to this, Bartlett and Preston [61] acknowledged that the CSR orientation of an organization could reduce the conflict of interest between different stakeholders, which, in turn, increases its financial stability. Moreover, the CSR activities of an organization may provide an additional financial resource as the creditors and investors in the current era also evaluate a business based on its social activities for the betterment of society [62]. Thus, a socially responsible organization is expected to access different capital sources [63].…”
Section: Csr and Financial Performancementioning
confidence: 99%
“…In the context of corporate sustainability, the management of these relationships and cooperation among stakeholders play a key role (Hörisch et al, 2014;Matinaro & Liu, 2017;Roca-Puig, 2019;Schaltegger, Lüdeke-Freund, & Hansen, 2012;Whelan & Fink, 2016). Not only do they provide insurance-like protection of the company's ability to sustain financial performance, they also contribute to corporate sustainability and long-term success (Suto & Takehara, 2020). Similarly, legitimacy theory offers a theoretical explanation for the positive effects of sustainability practices (Deegan, 2019;Dumay, De Villiers, Guthrie, & Hsiao, 2018;Silva, 2021).…”
Section: Literature Review and Working Hypothesesmentioning
confidence: 99%
“…Other studies reported similar results, by mentioning that stock price will be more stable when management earnings forecasts met or beaten (Kross et al, 2011;Merkley et al, 2013;Rezazadeh, 2020;Vahedi, 2020). Moreover, Suto, M. and Takehara, H. (2020) found that management earnings forecasts accuracy enhances the investor trust, and stock market stability which indirectly reflected in the reliability of stock prices. Another study reported that management manipulates earnings forecasts to affect the share price by providing optimistic forecasts in case of its desire to increase stock price and providing pessimistic forecasts if the desire to reduce share price.…”
Section: Multivariate Analysis (Regression Analysis and Hypotheses Testing)mentioning
confidence: 99%